KNOWLEDGE AND ATTITUDE WITH ADHERENCE TO FE TABLET CONSUMPTION IN ANEMIC ADOLESCENT GIRLS - Diani, Aisyah Amalia Putri; Amalia, Rize Budi; Sudaryanti, Lestari; Lestari, Pudji (UNIVERSITAS AIRLANGGA, 2024)
Background: Iron anemia could be prevented through the administration of Fe tablets (TTD). Several studies had shown that one of the obstacles often encountered in the Fe tablet administration program was the problem of compliance. The low compliance of Fe tablets consumption in adolescent girls was influenced by several factors, one of which was the knowledge of female students regarding the benefits of consuming Fe tablets. Knowledge affected the attitudes and behavior of adolescents in choosing food, consuming Fe tablets supplementation, and further affected the overall nutritional condition of individuals including the condition of anemia status. Objective: This study aimed to demonstrate the connection between attitudes and knowledge about adherence to Fe tablets use in anemic adolescents at Pondok Pesantren Mambaus Sholihin, Gresik District, East Java. Methods: This type of research was quantitative research with a cross-sectional design, sampling using the total sampling method. Method in this research was an analytical observational study with a cohort retrospective design. The samples in this study were 81 adolescent girls aged 15-17 years who experienced anemia. The variables used in this study were knowledge, attitude and compliance. The instruments used were questionnaires and checklist forms. Compliance with Fe tablet consumption was carried out for the last 3 months. Results: Most respondents had sufficient knowledge related to anemia and Fe tablets around (31.1%) and most responders had a positive attitude of (56.8%) most respondents were not compliant with the consumption of Fe tablets by (58.0%). After the chi square test, the significance value (p=0.002) was obtained, which means that statistically there is a significant relationship between knowledge and Fe tablet consumption, and (p=0.000) there is a significant relationship between attitude and Fe tablet consumption. Conclusion: The study concluded that among teenage girls attending the Mambaus Sholihin Islamic Boarding School, there was a relationship between knowledge and attitude regarding the intake of Fe tablets.